Sifat Fisik dan Preferensi Masyarakat terhadap Fusion Dessert Komersial Klappertaart Durian Katuk - Ira Handayani; Ndaru Prasastono (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2026)
This study aimed to determine the physical characteristics and consumer preferences of a commercial fusion dessert, durian–katuk klapertaart (Sauropus androgynus). An experimental method was employed using a Completely Randomized Design (CRD) with three different treatments. Organoleptic evaluation was conducted by 30 untrained panelists using a hedonic test. The data were analyzed using Analysis of Variance (ANOVA) followed by Duncan’s Multiple Range Test. The results showed that the substitution percentage in each treatment had a significant effect on consumer acceptance in terms of aroma, texture, color, and taste. Formulation F2 was the most preferred by the panelists. The physical characteristics of the F2 formulation were soft with a slightly fibrous texture, a moderately strong durian aroma, a fairly strong katuk aroma, a slightly dark green color, and a balanced sweet taste of durian and katuk.